CRITERIA FOR DETERMINING CASES INCOMPATIBLE FOR THE EXERCISE OF DEPUTY POWERS (TAMADDUN NURI JURNALI, 2025)
This article examines the criteria for identifying situations that are incompatible with the exercise of parliamentary powers. The specificity of this topic lies in the analysis of various factors, including legal, ethical and social aspects, that may affect the performance of parliamentary duties.